Socioeconomic determinants of the leprosy risk in Yunnan Province, China: a county-level spatiotemporal study - Qian, Jian; Ma, Yue; Wei, Yuxin; Peng, Zutong; Li, Wei; Zhang, Tao; Yin, Fei; Shui, Tiejun (Frontiers in Public Health, 2025)
BackgroundMaking leprosy history in low-burden countries is a crucial step in achieving the World Health Organization’s 2021–2030 Global Leprosy Strategy. Since leprosy has been contained at the national level in these countries, current efforts to eliminate leprosy have focused on specific leprosy high-risk areas. Quantifying the factors associated with leprosy risk would assist in identifying high-risk areas and the required efforts for leprosy elimination, which are still inadequate in these countries. To further progress a leprosy-free world, we investigated the associations between socioeconomic factors and the risk of leprosy in Yunnan Province, China.MethodsSocioeconomic factors and leprosy cases for 129 counties in Yunnan Province from 2004 to 2019 were collected. A spatiotemporal Bayesian model was used to evaluate the socioeconomic factors associated with leprosy risk.Results4,361 leprosy cases were reported from 2004 to 2019 in Yunnan. Negative associations between disposable income per capita of rural residents (RR = 0.947, 95% CI: 0.907, 0.989), population density (RR = 0.920, 95% CI: 0.894, 0.945), the number of students enrolled by regular secondary schools (RR = 0.990, 95% CI: 0.986, 0.994), and leprosy risk were found in Yunnan Province. The associations between the per capita product of the primary industry, proportion of male population, number of beds in health and medical institutions per 1,000 population, and leprosy risk were not significant.ConclusionThis study revealed the associations between socioeconomic factors and leprosy risk in a low-burden country. These findings suggest that subsequent leprosy elimination efforts in Yunnan Province should prioritize rural areas, particularly those with lower population density and lower economic levels among farmers. Additionally, it is crucial to actively target poor rural farmers as a high-risk group for leprosy through strengthened early detection, multidrug therapy, and health education.